2009
DOI: 10.1590/s0100-40422009000700028
|View full text |Cite
|
Sign up to set email alerts
|

Alcaloides iboga de Peschiera affinis (Apocynaceae) - Atribuição inequívoca dos deslocamentos químicos dos átomos de hidrogênio e carbono: atividade antioxidante

Abstract: Recebido em 18/10/08; aceito em 5/3/09; publicado na web em 26/8/09IBOGA ALKALOIDS FROM Peschiera affinis (APOCYNACEAE) -UNEQUIVOCAL 1 H AND 13 C CHEMICAL SHIFT ASSIGNMENTS. ANTIOXIDANT ACTIVITY. Six known alkaloids iboga type and the triterpen α-and β-amyrin acetate were isolated from the roots and stems of Peschiera affinis. Their structures were characterized on the basis of spectral data mainly NMR and mass spectra. 1D and 2D NMR spectra were also used to unequivocal 1 H and 13 C chemical shift assignments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…The antioxidant activity of the raw extract from the aerial parts of T. catharinensis was lower than that observed in root ethanolic extracts of this species (IC 50 = 100  μ g/mL) [32] but higher than that identified in ethanolic extracts of T. heyneana leaves (IC 50 = 537  μ g/mL) [33]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidant activity of the raw extract from the aerial parts of T. catharinensis was lower than that observed in root ethanolic extracts of this species (IC 50 = 100  μ g/mL) [32] but higher than that identified in ethanolic extracts of T. heyneana leaves (IC 50 = 537  μ g/mL) [33]. …”
Section: Resultsmentioning
confidence: 99%
“…Indole alkaloids have been previously described as exhibiting antioxidant activity [32, 34]. Studies showed that reactive oxygen species uptake activity in indole derivatives could be related to the exceptional redox property of the indole ring, which is especially conferred by the indole nitrogen [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained extract was filtered through qualitative filter paper and the solvent was removed by rotary evaporation under reduced pressure at temperatures below 45 • C. The resulting crude extract was then stored at 4 • C until further analysis. A portion of the crude methanolic extract (10 g) was fractioned by filter column chromatography over 100 g silica gel 60 (S) (Santos et al, 2009), and eluted with approximately 1 L of the solvents hexane, dichloromethane, ethyl acetate, and ethanol, in the order of increasing polarity, until a clear extract was obtained at the end of the elution. Pump pressure at approximately 5 bar was applied to accelerate the elution of the solvents.…”
Section: Extraction Methodology and Fractioningmentioning
confidence: 99%
“…Estudos químicos e farmacológicos têm grande importância em levantamento etnobotânicos, pois comprovam os efeitos medicinais e toxicológicos das espécies utilizadas. Dessa forma, diversos trabalhos já foram realizados nesse âmbito, como os estudos de Silva et al (2004); Baggio et al (2005); Moza (2005); ; Biavatti et al (2007); Pereira et al (2007); Moraes et al (2008); Nardin et al (2009) e Santos et al (2009). Contudo, pouco ainda tem sido estudado frente ao grande número de plantas com diversas potencialidades medicinais.…”
Section: Resultsunclassified